Enfoque comunicativo e processos motivacionais : uma análise da prática docente na aula de língua espanhola - Silva, Caroline Teixeira Fuão da (2017)
This research aims to increase knowledge about the Communicative language teaching and relate it with the motivational process of teachers of Spanish language. For this, the problem of research it is to investigate, as this professor, identifies himself as a mediator in the processes of teaching and learning, according to the focus of communication and through his motivational process. Considering aspects of literature, in accordance with the principles of focusing communicative and theories of motivation, we attempted to get to know the potentiality and limitation perceived by teachers about the focus of communication; examine the role of mediator, through the reasons to become a teacher of spanish and observe how the teacher applies its methodological strategies from the focus. This study was characterized as a qualitative approach, referred to as a case study. The instruments chosen were the implementation of three observations of classrooms and a semi-structured interview room with four native teachers of Spanish language, an Institute of Languages of Porto Alegre. For analysis and obtaining the results, we used the textual analysis of discourse, through the principles of Moraes (2014). The results showed that the principles of communicative approach helps the teacher in developing units and in the way applies the strategies of learning for the student to develop their communicative competence autonomously. In addition, the characteristics of the role of mediator provide the faculty better management of classrooms and the possibility of building social bond and affective between teacher and student, through his motivational process. In this way, the learning strategies developed by professor mediator opportunism the condition to explore aspects of interculturality in the lessons of Spanish language, as a way of social integration with intercultural behavior, through communication in the Spanish language. These three aspects found: professor mediator, learning strategies and interculturality, can be regarded as pillars in the improvement and updating of curricula of training, in preparation of plans customized methodology and the opportunity for social integration, with a view to an intercultural behavior in the teaching and learning of Spanish in our national context.